Study of The Local Wisdom Curriculum of Geopark Belitung to Support Local Cultural Values in Context of Natural Science Learning for Elementary School - Budiastra, A.A. Ketut; Puspitasari, Susy; Wicaksono, Iwan; Erlina, Nia (Advances in Social Sciences Research Journal, 2021)
In this article, the respondent's opinion is discussed about the effectiveness of the model of integrating local cultural values of the Belitung Geopark in learning science in elementary schools. The research design refers to research and development design (R&D) includes four stages of activity. However, this study discusses the results of a preliminary study on the content of the local cultural values of the Belitung Geopark in science learning in elementary schools. The population of this research is the teachers of elementary schools Dendang District and Simpang Pesak District, East Belitung Regency. The sample was selected by purposive sampling, namely 34 elementary school teachers and as many as 152 elementary school students in grade IV, grade V, and grade VI. The instruments used in the data collection process included questionnaires, interview guidelines, observation sheets, and student learning outcomes tests. The teacher's ability to plan to learn is measured using the teacher ability assessment tool (TAAT) I format. Meanwhile, the teacher's ability to teach is measured using the (TAAT) II format. From the results of this study, it concluded that (1) Implementation of the Geopark local wisdom curriculum is effective in improving student geopark learning outcomes in science learning in elementary schools; (2) The characteristics of science learning that are integrated with Geopark content can be implemented by the teacher; (3) The model of integrating local cultural values of the Belitung Geopark in learning science in elementary schools can realize the concept of science is fun in elementary school.